2012
DOI: 10.1590/s0100-69912012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Exame radiográfico convencional do tórax no diagnóstico de hérnia diafragmática pós-traumática

Abstract: The study showed that CXR is very useful in the initial diagnostic approach to PTDH. The difficulty is that diaphragmatic injuries, particularly after penetrating trauma, may initially go unnoticed, and without changes in the CXR images, diagnosis is made difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
4
0
4
Order By: Relevance
“…The addition of FU CXR for all right lobe donors is minimal in terms of cost and invasiveness. Although the traditionally reported sensitivity of CXR for traumatic diaphragmatic injuries is only 40%, a recent study by Hirano et al 19 found that suggestive findings such as hemidiaphragm elevation, pneumothorax, and hemothorax were present in 81% traumatic diaphragm injuries. Hemidiaphragm elevation accounted for 84% of all suspicious findings.…”
Section: Discussionmentioning
confidence: 96%
“…The addition of FU CXR for all right lobe donors is minimal in terms of cost and invasiveness. Although the traditionally reported sensitivity of CXR for traumatic diaphragmatic injuries is only 40%, a recent study by Hirano et al 19 found that suggestive findings such as hemidiaphragm elevation, pneumothorax, and hemothorax were present in 81% traumatic diaphragm injuries. Hemidiaphragm elevation accounted for 84% of all suspicious findings.…”
Section: Discussionmentioning
confidence: 96%
“…Quando tratada na ocasião do trauma têm taxa de mortalidade menor que 5%, contudo se diagnosticadas durante uma complicação, esta taxa pode aumentar para 48%. 2 As lesões assintomáticas são mais comuns no hemidiafragma esquerdo, explicado pela presença do fígado à direita, maior resistência à tensão do suture of the diaphragmatic defect and thoracic drainage. Had an uneventful recovery and was discharged on the fourth postoperative day.…”
Section: Discussionunclassified
“…Quando localizado à direita, tem maior mortalidade no local da ocorrência. 2,3 Os órgãos comumente herniados são estômago, cólon, omento e alças de delgado. 3,5 Os limites superiores da transição toracoabdominal são definidos pelo quarto espaço intercostal na face anterior, sexto espaço intercostal na face lateral do tórax e oitavo espaço na região dorsal.…”
Section: Discussionunclassified
See 2 more Smart Citations